2018
DOI: 10.1111/evo.13468
|View full text |Cite
|
Sign up to set email alerts
|

Comment on Amézquita et al. (2017) “Conspicuousness, color resemblance, and toxicity in geographically diverging mimicry: The pan-Amazonian frogAllobates femoralis

Abstract: Amézquita et al. (2017) recently concluded that species of the Allobates femoralis group are toxic to mice at levels equivalent to syntopic alkaloid-containing poison frogs, which they attributed to the presence of alkaloids in skin secretions. However, the chemical composition of skin secretions was not analyzed, and here we present additional data supporting the absence of alkaloids in skin secretions of the Allobates femoralis group. Instead, we suggest the observed toxicity was caused by the anesthetic ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…[32]. Because epibatidine is a highly toxic alkaloid (LD50 ~0.2 mg/kg; [43]), and A. femoralis is considered a non-toxic dendrobatid species ([44], but see [45] and [46]), we judged using the less toxic alkaloid sparteine (LD50 ~200 mg/kg; [47]) for this species. Sparteine is an alkaloid from plants of the genus Lupinus , which has a similar structure to epibatidine but belongs to the quinolizidine class (Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
“…[32]. Because epibatidine is a highly toxic alkaloid (LD50 ~0.2 mg/kg; [43]), and A. femoralis is considered a non-toxic dendrobatid species ([44], but see [45] and [46]), we judged using the less toxic alkaloid sparteine (LD50 ~200 mg/kg; [47]) for this species. Sparteine is an alkaloid from plants of the genus Lupinus , which has a similar structure to epibatidine but belongs to the quinolizidine class (Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, we initially collected 2 frogs from the Kaw Mountains in 2013, which were used for molecular analysis, but to increase sample size for alkaloid variability, we collected 6 additional frogs in 2014. Frogs were killed by deep-freezing to avoid possible contamination from killing agents (58). Livers were preserved in 95% ethanol, and whole skins were preserved in 100% methanol for subsequent alkaloid analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The use as an anuran death protocol is highly effective concerning lethality even when compared to other anesthetics PLOS ONE [20,21,31,32] besides to being considered a low-cost product and without restrictions on the purchase, facilitating access [12,18]. On the other hand, the use of anesthetics to kill frogs that will subsequently have their skins removed for the preparation of extracts used in biological tests or investigation of the chemical composition present in the integument can be a problematic factor due to the potential contamination [22].…”
Section: Plos Onementioning
confidence: 99%
“…Benzocainebased anesthetics are highly effective for both, anesthesia and death in amphibians, not requiring a large amount of the product to be able to kill them [12,[18][19][20][21]. However, recently, Saporito and Grant [22] found traces of the benzocaine substance coming from the Orajel © (liquid) product in skin extracts made from individuals of the species Melanophryniscus moreirae and Lithobates clamitans killed with the oral application of this anesthetic and concluded that the application directly in the mouth in certain species of anurans, may invalidate potential studies on the chemical composition of the extracts of these animals, signalling false positives, such as inaccurate detection of substances and/or incorrect information about potential biological activities. The authors gave as an example the study by Amézquita et al [23] who, through experiments, suggested that some populations of the frog Allobates femoralis showed higher toxicity in the extracts when used in mice and was considered by the authors to be from alkaloids present in the integument of this species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation